Migración y heterotopía en la obra de Nisa Forti (Altre Modernità, 2014)
This paper takes into account the novel La crisálida (1984) written by the Italian women writer Nisa Forti (1934-2009) emigrated to Argentina in 1948. The study analyses how writing presents migration’s experience through the appropriation of mechanisms related to heterotopy. By doing so, the novel advances a reformulation of utopian and dystopian relationships between original country and destination country.